Towards the elaboration of a diastratic model in historical analyses of koineization - Brown, Joshua (Sociolinguistic Studies, 2021)
The paper argues for further development of models of koineization in a historical perspective. The four processes inherent in koineization reported in Britain (2012a) are taken as a starting point to show how the question of discerning these phenomena in the past is inherently problematic, but not impossible. After discussing some issues in identifying these processes in a medieval context, the paper moves to previous analyses of diastratic variation in studies of koineization. Using the data available for late medieval Italy, emphasis is placed on how diastratic variation is discernible in three parameters of verb morphology arising in the resultant koine, focussing on medieval Milanese. These observations, in turn, lead to further elaboration of a diastratic component in order to broaden our understanding of language change.